2015
DOI: 10.1371/journal.pone.0126577
|View full text |Cite
|
Sign up to set email alerts
|

Specific Inhibitory Effect of κ-Carrageenan Polysaccharide on Swine Pandemic 2009 H1N1 Influenza Virus

Abstract: The 2009 influenza A H1N1 pandemic placed unprecedented demands on antiviral drug resources and the vaccine industry. Carrageenan, an extractive of red algae, has been proven to inhibit infection and multiplication of various enveloped viruses. The aim of this study was to examine the ability of κ-carrageenan to inhibit swine pandemic 2009 H1N1 influenza virus to gain an understanding of antiviral ability of κ-carrageenan. It was here demonstrated that κ-carrageenan had no cytotoxicity at concentrations below … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 30 publications
1
39
0
Order By: Relevance
“…It may affect the transmembrane and intracellular signaling processes involved in regulating virus expression. These results were supported by previous findings that viral protein synthesis was prevented by carrageenan, as inhibition was observed only when the compound was present during virus entry [ 23 ]. Damonte et al reported that the few attempts had been made to find anti-viral substances by mainly focusing on the screening of probable ribonucleic acid (RNA) synthesis inhibitors, such as ribavirin and other nucleoside analogs [ 9 ].…”
Section: Discussionsupporting
confidence: 89%
“…It may affect the transmembrane and intracellular signaling processes involved in regulating virus expression. These results were supported by previous findings that viral protein synthesis was prevented by carrageenan, as inhibition was observed only when the compound was present during virus entry [ 23 ]. Damonte et al reported that the few attempts had been made to find anti-viral substances by mainly focusing on the screening of probable ribonucleic acid (RNA) synthesis inhibitors, such as ribavirin and other nucleoside analogs [ 9 ].…”
Section: Discussionsupporting
confidence: 89%
“…Iota-carrageenan inhibits several viruses based on its interaction with the surface of viral particles, thus preventing them from entering cells and trapping the viral particles released from the infected cells. [8,9,10,11,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…They exhibit a wide range of physico-chemical properties that have found useful applications in food science, and the medical and pharmacological fields. The cell walls of marine algae are rich in sulfated polysaccharides, and, in particular, those with chemical structures similar to the glycosaminoglycans (GAGs) have exhibited significant antiviral activity (Damonte et al 2004;Pujol et al 2007;Shao et al 2015). Polysaccharide moieties of proteoglycans constitute complex molecules that may be capable of storing functional information for the cell.…”
Section: Introductionmentioning
confidence: 99%